Effects of the regulation of the dyadic interaction in argumentative tasks - Peralta, Nadia Soledad (2021)
The objective of this paper is to analyze the effects of the interactive regulation of dyadic situations on the argumentative abilities of the subjects in two types of tasks: ordering causes of social phenomena and taking position in front of dilemmatic situations. A quasi-experimental study was carried out, the pre-test and the post-test of the participants after the interaction were compared, constituting two groups; dyads with assistance from the interaction by the researcher (participation, evaluation and counter-argumentation) and dyads without assistance. The results show that the assistance produces significant effects in the